Investigation of pale shrimp disease in Pacific white shrimp (Litopenaeus vannamei) caused by Photobacterium damselae subsp. damselae in low salinity culture conditions - Niti Chuchird; Natnicha Chongprachavat; Wiranya Suanploy; Lalitphan Kitsanayanyong; Putsucha Phansawat; Arunothai Keetanon; Parattagorn Wimanhaemin; Tirawat Rairat (Aquaculture Reports)
Pale shrimp disease is a serious emerging disease affecting juvenile Pacific white shrimp (Litopenaeus vannamei) in the low salinity areas of Southern Thailand. The most prominent clinical sign is a uniformly pale body coloration, with a mortality rate of nearly 100 % in severe cases. This study aimed to identify the causative agents of this disease. The affected shrimp from the natural outbreak ponds were collected for disease investigation. The disease was proven to be transmissible, as feeding-challenged shrimp showed pale body characteristics. To demonstrate the bacterial etiology of the disease, bacteria were isolated from naturally diseased shrimp and identified using 16S rRNA gene sequencing. Pure cultures were inoculated into healthy shrimp. Among the different bacterial isolates (mainly Vibrio spp.), only Photobacterium damselae subsp. damselae (PDD) induced clinical signs of a pale body. Thus, PDD was examined for pathogenicity via immersion (105 CFU/mL) and oral gavage (107 CFU/shrimp) at 10 ppt. On day 7, the challenged shrimp showed pale body coloration, and the survival rates of both groups were 53 % and 10 %, respectively, whereas no mortality was observed in the control shrimp. Histologically, the hepatopancreatic tubules of the PDD-infected shrimp were atrophic, and lymphoid organ spheroids, myopathy, and hemocytic infiltration in the muscle were also evident. These histopathological changes are generally consistent with those observed in natural outbreaks. Consequently, our findings revealed that the enigmatic pale shrimp disease is caused by PDD, a hitherto unknown pathogen that causes massive shrimp mortality.